Islamic Religious Education Learning in Elementary School Plus at Islamic Boarding School - Hidayati Ali, Novia Rosyidah (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2025)
This study explores the implementation of Islamic Religious Education based on Islamic Boarding School teaching at Elementary School Plus of Al-Anwar Islamic Boarding School Paculgowang. The primary objective is to analyze how Islamic Boarding School-based learning methods are applied in elementary education and their impact on students’ academics and character development. This research employs a qualitative approach using a case study method, where data is collected through observations, interviews, and documentation. The findings reveal that Islamic Religious Education learning at this school adopts Islamic Boarding School-based methods, such as daily practices of sholat dhuha, memorization of short surahs, and congregational sholat dhuhur. Additionally, the curriculum integrates classical Islamic Boarding School books like Mabadi’ul Fiqih, Akhlakul Banin, and Tauhid, which provide students with a deeper understanding of Islamic teachings. Evaluation is conducted through oral and written tests, daily behavioral observations, and the sorogan method in kitab reading. The impact of Islamic Boarding School-based education is evident in students’ discipline in worship, respectful behavior, and harmonious social interactions between students, teachers, and parents. With these positive outcomes, this educational model can serve as a reference for other schools seeking to integrate Islamic Boarding School systems into elementary education curricula.